Peran sholat istikharah dalam penyembuhan mental - Daroini, Maiya Hasanatud - (Maliki Interdisciplinary Journal, 2025)
Mental health is an essential aspect of human life that relates to emotional, cognitive, and spiritual balance. In Islam, mental healing is not only achieved through medical approaches but also through worship that nurtures inner peace. One such practice is Shalat Istikharah, which serves as both a means of seeking divine guidance and a form of spiritual therapy for individuals experiencing confusion or psychological distress. This study discusses the role of Shalat Istikharah in mental healing from a psychoreligious perspective. The findings indicate that Istikharah helps reduce stress, enhance self-awareness, and strengthen faith and trust in Allah SWT. Furthermore, it fosters optimism, patience, and self-acceptance, core foundations of mental tranquility. Thus, Shalat Istikharah can function as an effective religious therapy for maintaining mental health among Muslims amid the challenges of modern life.